Faktor Penghambat Peran Dinas Dalam Pemberdayaan Petani Kopi di Desa Jernih Jaya - Mahendra, Rillo; Eriyanti, Fitri (Indo-MathEdu Intellectuals Journal, 2025)
The potential of Jernih Jaya Village in producing coffee is present, where there is a role of the relevant agency towards coffee farmers in Jernih Jaya Village, but the results are not yet optimal. The empowerment roles carried out by the agency include, first, providing assistance such as coffee seed support, coffee husking machines, and fertilizer assistance. Second, socialization activities, training, and mentoring. Third, promotion and management of geographic indication (IG) certification. This research aims to describe the inhibiting factors of the role of the Department of Plantation and Livestock in empowering coffee farmer communities in Jernih Jaya Village. This type of research is qualitative with a descriptive method. Data collection was conducted through interviews, observation, and documentation. The research findings indicate that the inhibiting factors for the role of the agency include a shortage of skilled human resources, where the agency only has a few employees who can lead empowerment activities. When these employees are not available, the agency struggles to find replacements. The limitations in budget or funding mean that the budget constraints faced by the agency affect the implementation of empowerment activities. The difference in perspective between the agency and coffee farmers has led to resistance from farmers to implement the agency's directives. The benefit of this research is to describe the inhibiting factors for the role of the agency and the efforts that can be made by the agency to overcome them.